CEDAW: The Challenges of Enshrining Women's Equality in International Law. (4th May 2018) - Mullins, Lauren Bock
Abstract : While women's rights are more of a recent development in international human rights law, the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) was the first international agreement to declare women's rights as human rights. This article is both a description and an analysis of the Convention and the Optional Protocol, the reservations, general problems, and the issue of cultural relativism. An analysis of the United States in relation to CEDAW in terms of particular state issues of enforcement, ratification, and reservations brings to light possible solutions for further establishment of rights through CEDAW, including the organization of an interstate forum.